Bioeconomic study of Chlorella vulgaris in outdoor tank culture by using different types of fertilizer - Tunku Azmir Shah, Tunku Ainna; Loo, Bee Gan; Zulkifly, Shahrizim; Omar, Hishamuddin; Ismail, Ahmad (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2014)
Four different culture mediums that were Bold Basal, commercial fertilizer, modified fertilizer and modified Bold Basal were used to cultivate Chlorella sp. in outdoor tanks. The modified fertilizer was formulated according to the NPK ratio in Bold Basal medium (control). Clewat 32 (0.01 g/L) was used in modified Bold Basal to replace the micronutrient in Bold Basal medium. The growth of C. vulgaris in outdoor culture was determined daily by cell count and dry weight every two days. The result of this study shows that, culture in modified fertilizer has no effect in improving the total production in outdoor culture. Meanwhile, culture in Bold Basal medium has relatively higher productivity (1.14 g/m2/day) at its optimum if compared to modified Bold Basal medium at 1.08 g/m2/day. Thus, the production cost per gram in 100 L outdoor tank culture was less expensive for Bold Basal medium which is about RM 21.13/g but moderately higher in modified fertilizer (RM 26.75/g). Bioeconomic studies revealed the weakness particularly with respect to the biological component. Possible weaknesses in the biological component are low productivity, unsuitable strain of Chlorella sp., weather, culture technique and scale of production.